Can the National Surgical Quality Improvement Program Provide Surgeon-Specific Outcomes?. Issue 2 (February 2015) - Kuhnen, Angela H.; Marcello, Peter W.; Roberts, Patricia L.; Read, Thomas E.; Schoetz, David J.; Rusin, Lawrence C.; Hall, Jason F.; Ricciardi, Rocco
Abstract : BACKGROUND: Efforts to improve the quality of surgical care and reduce morbidity and mortality have resulted in outcomes reporting at the service and institutional level. Surgeon-specific outcomes are not readily available. OBJECTIVE: The aim of this study is to compare surgeon-specific outcomes from the National Surgical Quality Improvement Program and 100% capture institutional quality data. DESIGN: We conducted a cohort study evaluating institutional and surgeon-specific outcomes following colorectal surgery procedures at 1 institution over 5 years. PATIENTS: All patients who underwent an operation by a colorectal surgeon at Lahey Hospital & Medical Center from January 1, 2008 through December 31, 2012 were identified. MAIN OUTCOME MEASURES: Thirty-day mortality, reoperation, urinary tract infection, deep vein thrombosis, pneumonia, superficial surgical site infection, and organ space infection were the primary outcomes measured. ANALYSIS: We compared annual and 5-year institutional and surgeon-specific adverse event rates between the data sets. In addition, we categorized individual surgeons as low-outlier, average, or high-outlier in relation to aggregate averages and determined the concordance between the data sets in identifying outliers. Concordance was designated if the 2 databases classified outlier status similarly for the same adverse event category. RESULTS: In the 100% capture institutional data, 6459 operative encounters were identified in comparison with 1786 National Surgical Quality Improvement Program encounters (28% sampled). Annual aggregate adverse event rates were similar between the institutional data and the National Surgical Quality Improvement Program. For annual surgeon-specific comparisons, concordance in identifying outliers between the 2 data sets was 51.4%, and gross discordance between outlier status was in 8.2%. Five-year surgeon-specific comparisons demonstrated 59% concordance in identifying outlier status with 8.2% gross discordance for the group. LIMITATIONS: The inclusion of data from only 1 academic referral center is a limitation of this study. CONCLUSIONS: Each surgeon was identified as a "high outlier" in at least 1 adverse event category. Comparisons at the annual and 5-year points demonstrated poor concordance between our 100% capture institutional data and the National Surgical Quality Improvement Program data.